Reduction of arthritis following intra-articular administration of an adeno-associated virus serotype 5 expressing a disease-inducible TNF-blocking agent. Issue 9 (15th March 2007) - Adriaansen, J; Khoury, M; de Cortie, C J; Fallaux, F J; Bigey, P; Scherman, D; Gould, D J; Chernajovsky, Y; Apparailly, F; Jorgensen, C; Vervoordeldonk, M J B M; Tak, P P
Abstract : Background: In the context of preclinical development, we studied the potential of intra-articular gene delivery using a recombinant adeno-associated virus 5 (rAAV5) encoding a chimeric human tumour necrosis factorα (TNFα) soluble receptor I linked to a mouse immunoglobulin heavy chain Fc portion (TNF receptor I; TNFRI-Ig). Methods: Expression was under control of a nuclear factor kappa B (NFκB)-responsive promoter and compared with a cytomegalovirus (CMV) promoter (rAAV5.NFκB-TNFRI-Ig and rAAV5.CMV-TNFRI-Ig, respectively). Results: Fibroblast-like synoviocytes transduced in vitro with rAAV5.NFκB-TNFRI-Ig were able to produce TNFRI-Ig protein in response to several stimuli, and this was inhibited upon treatment with a specific NFκB blocking agent. A bioassay revealed that the synthesised TNFRI-Ig was bioactive, showing a higher affinity for human than for rat TNFα. Transcription of the transgene and protein production were detectable in joints injected with both constructs. No dissemination of the vector was observed outside the joints. A significant reduction in paw swelling was seen in rats treated with rAAV5.NFκB-TNFRI-Ig. This clinical effect was accompanied by a decrease in pro-inflammatory cytokine levels and an increase in IL10 expression in the synovium. Conclusion: These results provide evidence that intra-articular gene therapy using rAAV5 encoding TNFRI-Ig may be a safe and feasible approach for the treatment of rheumatoid arthritis. The higher affinity for human TNFα suggests that in patients with rheumatoid arthritis the therapeutic effect might be even more pronounced than in rat adjuvant arthritis.